Pengembangan komponen pembelajaran bahasa Arab di madrasah aliyah - Khasairi, Moh. (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
This article discusses the development of learning components in the preparation of designing an Arabic language learning system in Madrasah Aliyah. Various development models can be utilized in designing learning systems, such as the Kemp Model, Banathy Model, PPSI Model, Dick and Carey Model, and the Almisri Model. The Almisri Model applies the following steps in designing Arabic language learning: needs analysis, formulation of needs and competencies, materials development, media and strategy development, and evaluation development. The development of an Arabic language learning system in Madrasah Aliyah must consider the characteristics of Arabic as a communication tool and its Islamic contexts, which should be taught in an integrated manner.